2022
DOI: 10.1002/mus.27558
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase 2 study ofACE‐083, amuscle‐promotingagent, in facioscapulohumeral muscular dystrophy

Abstract: Introduction/Aims: Facioscapulohumeral muscular dystrophy (FSHD) is a slowly progressive muscular dystrophy without approved therapies. In this study we evaluated whether locally acting ACE-083 could safely increase muscle volume and improve functional outcomes in adults with FSHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…One example is the phase I/IIA clinical trial for the use of a follistatin construct introduced via an adeno-associated virus for the treatment of Becker muscular dystrophy [ 108 ]. Recombinant follistatin has also been developed, such as ACE-083, although results on its efficacy against facioscapulohumeral muscular dystrophy conditions have not been promising [ 107 , 109 ]. Furthermore, because other isoforms of activin and inhibin have not been identified as relevant in PAH conditions, other agents that could restore the balance of activin/inhibin signaling have not been thoroughly investigated in clinical settings.…”
Section: Clinical Landscape Of Activin-targeting Treatments In Pahmentioning
confidence: 99%
“…One example is the phase I/IIA clinical trial for the use of a follistatin construct introduced via an adeno-associated virus for the treatment of Becker muscular dystrophy [ 108 ]. Recombinant follistatin has also been developed, such as ACE-083, although results on its efficacy against facioscapulohumeral muscular dystrophy conditions have not been promising [ 107 , 109 ]. Furthermore, because other isoforms of activin and inhibin have not been identified as relevant in PAH conditions, other agents that could restore the balance of activin/inhibin signaling have not been thoroughly investigated in clinical settings.…”
Section: Clinical Landscape Of Activin-targeting Treatments In Pahmentioning
confidence: 99%
“…Another follistatin-based fusion protein, ACE-083, also induced localized skeletal muscle hypertrophy and increased focal force generation in a mouse model [149]. However, in a phase II trial of ACE-083, treatment increased muscle mass but did not improve functional outcomes [150]. Associated virus (AAV) serotype 1.…”
Section: Follistatin Fusion Protein and Gene Therapymentioning
confidence: 99%
“…Often, a single trial does not provide a straightforward answer, as myostatin inhibition failed for different reasons in different trials [ 139 ]. Importantly, circulating baseline levels of myostatin are higher in FSHD than in DMD, and the ACE-083 trial demonstrated significant muscle hypertrophy (without an increase in strength) in treated FSHD patients [ 36 ]. Thus, it is conceivable that in combination with a DUX4-targeting therapy, myostatin inhibition might increase muscle function as well as size in FSHD.…”
Section: Dux4-independent Approachesmentioning
confidence: 99%
“…The creation of FSHD-specific therapeutics has been understandably hampered by these challenges, and in the interim, easier avenues have been explored, including compensatory treatments to improve muscle strength or health [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] ( Identifiers: NCT02927080, NCT02603562), immunomodulation ( Identifier: NCT02579239), and most recently, the repurposed FDA-approved drug losmapimod [ 37 ] ( Identifiers: NCT04003974, NCT04264442). Thus far, these treatments have either failed or yielded underwhelming results in clinical trials.…”
Section: Introductionmentioning
confidence: 99%